Crystal structure of 2-methyl-N-{[2-(pyridin-2-yl)ethyl]carbamothioyl}- benzamide - Ameram, Nadiah; Adam, Farook (International Union of Crystallography, 2015)
In the title compound, C16H17N3OS, a benzoyl thiourea derivative, the planes of the pyridine and benzene rings are inclined to one another by 66.54 (9). There is an intramolecular N—H O hydrogen bond present forming an S(6) ring motif. In the crystal, molecules are linked via pairs of N— H N hydrogen bonds, forming inversion dimers, which are reinforced by pairs of C—H S hydrogen bonds. The dimers are linked via C—H interactions, forming ribbons along [010].